Alternative splicing of a human alpha-tropomyosin muscle-specific exon: identification of determining sequences. - Graham, I R (1992)
The human alpha-tropomyosin gene hTMnm has two mutually exclusive versions of exon 5 (NM and SK), one of which is expressed specifically in skeletal muscle (exon SK). A minigene construct expresses only the nonmuscle (NM) isoform when transfected into COS-1 cells and both forms when transfected into myoblasts. Twenty-four mutants were produced to determine why the SK exon is not expressed in COS cells. The results showed that exons NM and SK are not in competition for splicing to the flanking exons and that there is no intrinsic barrier to splicing between the exons. Instead, exon SK is skipped whenever there are flanking introns. Splicing of exon SK was induced when the branch site sequence 70 nucleotides upstream of the exon was mutated to resemble the consensus and when the extremities of the exon itself were changed to the corresponding NM sequence. Precise swaps of the NM and SK exon sequences showed that the exon sequence effect was dominant to that of intron sequences. The mechanism of regulation appears to be unlike that of other tropomyosin genes. We propose that exclusion of exon SK arises because its 3' splicing signals are weak and are prevented by an exon-specific repressor from competing for splice site recognition.